“Auditoria de gestión y su incidencia en la gestión administrativa de las áreas operativas de la empresa sociedad agrícola y comercial cencerro cia. ltda. periodo - Villaruel Cando, Selena Carolina (2022)
This thesis consists of the preparation of a Management Audit for an agricultural production company, which will allow to understand the existing needs in the different areas and their correlation. . The general objective of the study of this Management Audit is that it will serve as a basic instrument to establish the degree of economy, effectiveness and efficiency in the use of the resources available in the company, promote the optimization of the levels of efficiency, effectiveness in the decision making of the Management, determine the fulfillment of the objectives and goals formulated by the Management, as well as the elaboration of new goals and satisfy the needs of customers. For the development of this thesis, information has been collected from internal sources of the company, interviews and surveys have been conducted with its collaborators and managers, ratios and financial indicators have been analyzed and evaluated, in order to determine the successes and shortcomings in its business dynamics. By developing this topic, it has been concluded that it will be possible to raise the level of organization, administration and control of the operations that are carried out within the company and in this way it will allow to achieve established objectives with less time and cost, improving its competitiveness and productivity.